Digital Media vs Traditional Promotion: The Changing Dynamics of Silk Road Tourism Marketing in Uzbekistan - Fayzullayeva Gulchexra (Studi Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study aims to examine how digital marketing platforms influence tourist behavior and travel decisions in Uzbekistan, particularly in relation to Silk Road tourism, compared to traditional promotional channels. Methodology: A quantitative approach was employed using survey data collected from 44 respondents via a structured online questionnaire. Data were analyzed using SPSS, with linear regression used to assess relationships between heritage-related factors and tourism behaviors, and descriptive analysis to evaluate the influence of promotional channels. Results: The percentage mentioned in your findings is 45.5%, which represents the proportion of travel decisions influenced by social media platforms such as Instagram, YouTube, and TikTok. Conclusions: The study concludes that digital marketing is essential for enhancing Uzbekistan’s tourism competitiveness. Social media-driven strategies and interactive platforms are more effective than traditional promotion, and combining these with heritage preservation and accessibility can maximize tourist engagement. Limitations: The study is limited by its small sample size (44 respondents) and focus on specific Silk Road tourism destinations, which may limit generalizability to other regions or larger populations. Contribution: This research provides insights for policymakers and tourism stakeholders on optimizing digital marketing strategies to enhance destination image, attract global visitors, and increase engagement with Silk Road tourism in Uzbekistan.